The Impact of Mis-Centering On CT Number Uniformity and Linearity in CT Simulator (International Journal of Scientific Research in Science and Technology, 2025)
This aim of this study is investigating the effect of mis-centering on computed tomography (CT) number uniformity and linearity in CT simulator. The current study used two phantoms: the GE water phantom for CT number uniformity evaluation, and the ACR Gammex 467 phantom for CT number linearity evaluation. The evaluations of CT number uniformity and linearity were conducted at y-axis with variations of -15, -10, -5, 0, 5, 10, and 15 mm, and with tube voltage variations of 80, 100, 120, and 140 kVp. The results demonstrated that mis-centering affects CT number uniformity. If the y-axis position increases, then CT number uniformity increases. However, mis-centering does not affect CT number linearity.
Keywords: mis-centering; CT simulator; CT number uniformity; CT number liniarity